Microbial quality of leafy green vegetables grown or sold in Accra metropolis, Ghana - Quansah, J.K.; Kunadu, A.P.H.; Saalia, F.K.; Díaz-Pérez, J.; Chen, J. (Food Control, 2018)
Samples of two exotic (lettuce and cabbage), and four indigenous (African spinach, African eggplant leaves, roselle leaves, and jute leaves) leafy green vegetables were collected from 50 vegetable farms in 12 farming areas (n = 175) and 37 sellers in 4 major market centers (n = 153) in Accra metropolis, Ghana. Microbial quality of collected samples was assessed by isolation of Salmonella and enumeration of aerobic bacteria, yeasts and molds, fecal coliforms, and enterococci. Mean aerobic bacteria, yeast and mold, fecal coliform, and enterococcus counts on collected vegetables were 8.80, 4.95, 4.90, and 3.67 log CFU/g, respectively. Approximately 75.4% of the vegetables from 96.0% of the vegetable farms and 84.3% of the vegetables from 97.3% of the vegetable sellers tested positive for enterococci, and 81.1% of the vegetables from 96.0% of the farms and 83.7% of the vegetables from 94.6% of the vegetable sellers tested positive for fecal coliforms. Salmonella were isolated from 5.1% of the vegetables from 16.0% of the vegetable farms and 15.7% of the vegetables from 24.3% of the vegetable sellers. Vegetable source and type had significant influence on the microbial counts. Results revealed that the sampled leafy green vegetables had poor microbial quality. Consumption of fresh leafy green vegetables without sanitizing or heat treatment should be discouraged.
Keywords: Indigenous vegetables; Cabbage; Lettuce; Farming areas; Market centers